What's the buzz? : keeping bees in flight - Wilcox, Merrie-Ellen (Orca footprints., 2015)
"Whether they live alone or together, in a hive or in a hole in the ground, bees do some of the most important work on the planet: pollinating plants. [This book] celebrates the magic of bees--from swarming to dancing to making honey--and encourages readers to do their part to keep the hives alive"--Amazon.com.